Separatism In The Perspective Of International Law And National Security: A Case Study Of The Armed Criminal Group (Kkb) In Papua - Chehafni Damanik; Panji Suwarno; Bayu Asih Yulianto; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The separatist movement in Papua, known as the Armed Criminal Group (KKB), has been a phenomenon in recent years. The KKB is a group of armed individuals advocating for the independence of West Papua from Indonesia. They engage in a series of activities including attacks on security forces, extortion, facility burnings, and human rights violations. Addressing the separatist movement of the KKB in Papua involves efforts to resolve the conflict peacefully, promote dialogue, strengthen regional autonomy, and address the root causes of the conflict. Long-term solutions require collaboration between the Indonesian government, Papuan community leaders, and separatist groups willing to adopt peaceful political approaches and respect international law. This paper will investigate the issue of separatism in the context of international law, focusing on the case study of the armed criminal group in Papua. The research aims to analyze the international legal responses to separatist movements that employ violence and illegal methods to achieve their goals, involving the analysis of international law concerning state sovereignty, human rights, and enforcement of international law. The data used in this study includes international legal instruments in decision-making.